S-Ketamine attenuates inflammatory effect and modulates the immune response in patients undergoing modified radical mastectomy: A prospective randomized controlled trial - Zhang, Junxia; Ma, Qian; Li, Wenbin; Li, Xiaohui; Chen, Xuexin (Frontiers in Pharmacology, 2023)
Objective: The purpose of this study was to investigate the impact of varying dosages of S-ketamine on perioperative immune-inflammatory responses in patients undergoing modified radical mastectomy (MRM). Methods: This is a prospective, randomized, controlled trial. A total of 136 patients with American Society of Anesthesiologists status I/II scheduled for MRM were enrolled and randomly assigned into groups to receive control (C), or one of three different doses (0.25 [L-Sk], 0.5 [M-Sk], or 0.75 [H-Sk] mg/kg) of S-ketamine. Primary outcome was the cellular immune function and inflammatory factors before anesthesia, at the end (T1) and 24 h (T2) after surgery. Secondary outcomes included the Visual Analogue Scale (VAS) score, opioid consumption, rate of remedial analgesia, adverse events. Results: The percentage and absolute counts of CD3+ and CD4+ cells in group L-Sk, M-Sk and H-Sk were higher than group C both at T1 and T2, moreover, pairwise comparison revealed the percentage in group H-Sk were higher compared to L-Sk and M-Sk groups, (p < 0.05). The ratio of CD4+/CD8+ were lower in group C at T1 and T2 than that in group M-Sk and H-Sk (p<0.05). There was no significant difference both in percentage and absolute counts of natural killer (NK) cells and B lymphocytes among four groups. While compared with the group C, the concentrations of white blood cells (WBC), neutrophils (NEUT), hypersensitive C-reactive protein (hs-CRP), the ratios of neutrophil/lymphocyte (NLR), systemic inflammation response index (SIRI) and systemic inflammation index (SII) at T1 and T2 in different doses S-ketamine groups were significantly lower and the lymphocytes were significantly higher, and the ratio of SIRI, NLR at T2 in group M-Sk was lower than group L-Sk (p<0.05). Additionally, a significantly decreased in VAS score, opioids consumption, rates of remedial analgesia and adverse events were observed in both M-Sk and H-Sk groups. Conclusions: Collectively, our studies established that S-ketamine can reduce opioids consumption, decrease postoperative pain intensity, exert systemic anti-inflammatory and may attenuate immunosuppression in patients undergoing MRM. Moreover, we found that the effects of S-ketamine are related to the dose used, with significant differences observed in 0.5 or 0.75 mg/kg of S-ketamine.